A Red Thermally Activated Delayed Fluorescence Emitter Simultaneously Having High Photoluminescence Quantum Efficiency and Preferentially Horizontal Emitting Dipole Orientation. (25th February 2020) - Gong, Xu; Li, Pan; Huang, Yu‐Hsin; Wang, Chun‐Yu; Lu, Chen‐Han; Lee, Wei‐Kai; Zhong, Cheng; Chen, Zhanxiang; Ning, Weimin; Wu, Chung‐Chih; Gong, Shaolong; Yang, Chuluo
Abstract: The development of red thermally activated delayed fluorescence (TADF) emitters having excellent optoelectronic properties and satisfactory electroluminescence efficiency is full of challenges due to strict molecular design principles. Two red TADF molecules, 3‐(9, 9‐dimethylacridin‐10(9 H )‐yl)acenaphtho[1, 2‐b]quinoxaline‐9, 10‐dicarbonitrile and 3‐(2, 7‐dimethyl‐10 H ‐spiro[acridine‐9, 9′‐fluoren]‐10‐yl)acenaphtho[1, 2‐b]quinoxaline‐9, 10‐dicarbonitrile, are developed by adopting a donor–acceptor molecular architecture bearing an electron‐accepting acenaphtho[1, 2‐b]quinoxaline‐9, 10‐dicarbonitrile (ANQDC) moiety and a 9, 9‐dimethyl‐9, 10‐dihydroacridine or 2, 7‐dimethyl‐10 H ‐spiro[acridine‐9, 9′‐fluorene] electron donor. The combined effects of rigid and planar D/A moieties and highly steric hindrance between D and A groups endow both molecules with high rigidity to suppress nonradiative decay processes, resulting in high photoluminescence quantum efficiencies (ΦPL s) of up to 95%. Attributed to the linear and planar acceptor motif and rod‐like molecular configuration, both emitters achieve high horizontal ratios of emitting dipole orientation of ≈80%. The organic light‐emitting diodes (OLEDs) based on both emitters exhibit red emissions peaking at ≈615 nm and successfully afford ultrahigh electroluminescence performance with an external quantum efficiency of nearly 28% and a power efficiency of above 50 lm W −1, on par with the state‐of‐the‐art device efficiency for red TADF OLEDs. This presents a feasible design strategy for excellent TADF emitters simultaneously possessing high ΦPL s and horizontally aligned emitting dipoles. Abstract : An ultrahigh‐efficiency red thermally activated delayed fluorescence (TADF) OLED with an external quantum efficiency of nearly 28% and a power efficiency of exceeding 50 lm W −1 is realized. The OLEDs incorporate excellent red TADF emitters, simultaneously exhibiting 95% photoluminescence quantum efficiency and preferentially horizontal emitting dipole orientation.